INCREMENTO DE LA PRODUCTIVIDAD POR DOSIFICACIONES DE FERTILIZACIÓN QUÍMICA EN TABACO (Nicotiana tabacum L.) EN RESPUESTA DE LOS PARÁMETROS FISIOLÓGICOS DE LA HOJA - Vega Armas, Jenniffer Arianna (2023)
Tobacco crop as any other crop needs to supply its nutritional needs to guarantee a good yield for the producer. The objective of this research was to evaluate the increase in productivity by chemical fertilization dosages in tobacco (Nicotiana tabacum L.) in response to the physiological parameters of the leaf. The trial was conducted at the Experimental Campus "La María" of the State Technical University of Quevedo, located at km 7.5 of the Quevedo - El Empalme road.